Characteristics of AC-WC Asphalt Concrete Mixtures with Polystyrene Addition - Fahmi, Rizky Hadijah; Erdiansa, Andi; Nursamiah, Nursamiah; Fattah, Abdul (Politeknik Negeri Ujung Pandang, 2023)
The top layer of pavement that functions as a wear layer is called AC-WC/ Laston. Improving the quality of flexible pavement continues to be developed in order to create transportation support facilities that are safe, strong and durable, but still economical. The use of additives is one way out that can be done in order to get a high quality product. The purpose of this research is to identify the optimum asphalt content to be used in the manufacture of polystyrene asphalt mixtures and to determine the characteristics of asphalt mixtures using polystyrene additives. The method used was to add polystyrene in the form of styrofoam which had previously been dissolved using gasoline into hot asphalt with a percentage of polystyrene mixture of 3.0%, 3.5%, 4.0%, 4.5% and 5.0% of the optimum asphalt content used. Based on the results of testing specimens with additional polystyrene, VIM and VMA values increased at levels of 3.0% to levels of 4.5% exceeding the upper limit of VIM specifications, but still within specifications. The stability value increased along with the increase of polystyrene from 3.0% to 5.0%, where this value meets the specifications. The flow value increases from 3.0% to 3.45% levels exceeding the upper limit of the specification then decreases after 3.45% levels to 5.0% levels where the flow value meets specifications. The conclusion that can be drawn is that the addition of polystyrene mixture in AC-WC can increase the hardness level of the Laston mixture.